Deviant Spirits in West Malaysian Factories - McLellan, Susan (Anthropologica, 2022)
This paper examines spirit possession among Malay female factory workers and shows the way in which a "normal" village reaction to stress in rural areas has been transformed into "deviance" by foreign owned transnational corporations operating in the new urban industrial estates.